Design Of The Organizational Structure And Coordination Of An Observatory Based On Collective Intelligence - Bohorquez Arévalo, Luz Esperanza; Castillo Rodríguez, Nelson Stiven; Farfán González, Mónica Sofia (Ingeniería Solidaria, 2020)
Introduction: This article is the product of research developed within the framework of the Emple-ap Project, throughout 2019 at the School of Industrial Engineering, Universidad Distrital Francisco Jose de Caldas. Problem: Limitations in the use of traditional hierarchical structures for the management of organizations based on control hierarchies, due to their difficulty in operating efficiently in human social systems (HSS). Objective: To generate a general proposal to understand the structure and organizational management for the observatory of employability of the Pacific Alliance (PA) supported by collective intelligence (CI) and high reliability organization (HRO). Methodology: The methodology for the development of the proposal is supported on grounded theory, in which the design emerges from the statements made in previous research. Results: Based on the results of the review, it presents a proposal for organizational structure for the observatory, emphasizing the alternatives to divide and coordinate the work and the important characteristics of the structure to facilitate the exploitation of available resources. Conclusion: The CI and reliable organizations, are a different and decentralized way of management in organizations that allow you to create more flexible and robust systems. This study creates a general outline of the characteristics and main preconditions that must have a system based on CI. Originality: The main contribution of this research lies in the design of an organizational structure, different from the traditional hierarchical structure, supported by CI for the management of an entire organization. Limitations: Currently, there are no great advances with respect to organizational structures or alternatives to the traditional hierarchies of control, despite limitations in information processing and the impact that has on performance.